A Meta‐Analysis of Supply Chain Integration and Firm Performance. Issue 2 (16th April 2013) - Leuschner,, Rudolf; Rogers, Dale S.; Charvet, François F.
<x xml:space="preserve">Abstract</x> As supply chain activities become more dispersed among customers, suppliers and service providers, there is an increased need for customers and suppliers to work together more closely. Supply chain integration (SCI) has been a highly researched topic during the last 20 years. A meta‐analytic approach is used to provide a quantitative review of the empirical literature in SCI, and examines relevant design and contextual factors. Eighty independent samples across 86 peer‐reviewed journal articles, yielding a total of 17, 467 observations, were obtained and analyzed. While general support exists in favor of the positive impact of SCI on firm performance in the literature, this research helps clarify mixed findings that presently exist. Our results indicate that there is a positive and significant correlation between SCI and firm performance. Additional subgroups and moderators are tested and provide nuanced views of the scope and specific dimensions of SCI, firm performance and their relationships.